2022
DOI: 10.1590/1806-9282.20211188
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of serum levels of galanin and obestatin in patients with gastric cancer

Abstract: OBJECTIVE: Gastric cancer ranks the third among the cancer-related deaths. It is diagnosed at advanced stage in many patients due to malignant proliferation and has a poor prognosis. Currently, no instrument or biomarker has been proven to diagnose the disease before the advanced stages. This study aimed to measure the serum levels of galanin and obestatin, which were examined in various studies including cancer studies, and to discuss their diagnostic value in gastric cancers. METHODS: In this study, 30 adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…One of the most used methods in diagnosing and following many diseases is biomarkers. 23 - 25 These markers can be used alone or with other auxiliary methods. Biomarkers play a critical role in the diagnosis of the disease, early recognition of organ dysfunction, disease risk classification, prognosis, and patient management.…”
Section: Methodsmentioning
confidence: 99%
“…One of the most used methods in diagnosing and following many diseases is biomarkers. 23 - 25 These markers can be used alone or with other auxiliary methods. Biomarkers play a critical role in the diagnosis of the disease, early recognition of organ dysfunction, disease risk classification, prognosis, and patient management.…”
Section: Methodsmentioning
confidence: 99%
“…compared to healthy persons, serum galanin levels decreased in patients with stomach cancer. Study concluded that serum galanin levels could be used as a potential biomarker in the detection of stomach cancer [12]. Galanin has been demonstrated to serve as a regulatory peptide within ovary, controlling preovulatory impulses of LH and prolactin and as well as regulating steroidogenesis in ovarian tissue.…”
Section: Journal Of University Of Anbar For Pure Science (Juaps)mentioning
confidence: 99%